Marine protected areas enhance structural complexity but do not buffer the consequences of ocean warming for an overexploited precious coral. Issue 5 (23rd January 2019) - Montero‐Serra, Ignasi; Garrabou, Joaquim; Doak, Daniel F.; Ledoux, Jean‐Baptiste; Linares, Cristina
Abstract: Global warming and overexploitation both threaten the integrity and resilience of marine ecosystems. Many calls have been made to at least partially offset climate change impacts through local conservation management. However, a mechanistic understanding of the interactions of multiple stressors is generally lacking for habitat‐forming species; preventing the development of sound conservation strategies. We examined the effectiveness of no‐take marine protected areas (MPAs) at enhancing structural complexity and resilience to climate change on populations of an overexploited and long‐lived octocoral. We used long‐term data over eight populations, subjected to varying levels of disturbances, and Integral Projection Models to understand how the overfishing and mass‐mortality events shape the stochastic dynamics of the Mediterranean red coral Corallium rubrum . Marine protected areas largely reduced colony partial mortality (i.e. shrinkage), enhancing the structural complexity of coral populations. However, there were no significant differences in individual mortality or population growth rates between protected and exploited populations. In contrast, warming had detrimental consequences for the long‐term viability of red coral populations, driving steady declines and potential local extinctions due to sharp effects in survival rates. Stochastic demographic models revealed only a weak compensatory effect of MPAs on the impacts of warming. Policy implications . Our results suggest that marine protected areas (MPAs) are an effective local conservation tool for enhancing the structural complexity of red coral populations. However, MPAs may not be enough to ensure red coral's persistence under future increases in thermal stress. Accordingly, conservation strategies aiming to ensure the persistence and functional role of red coral populations should include management actions at both local (well‐enforced MPAs) and global scales (reductions in greenhouse gas emissions). Finally, this study unravels the divergent demographic consequences that can arise from multiple stressors and highlights the key role of demography in better understanding and predicting the consequences of combined impacts for vulnerable ecosystems.